Risk Level Analysis of Pt Bank Syariah Indonesia Tbk Shares on the Bibit Application - Sukma Ayu Mustika (Journal of Economic and Business Analysis, 2023)
Abstract: The aim of this research is to analyze the level of risk in investing in shares of PT Bank Syariah Indonesia Tbk (BRIS) on the Bibit application. The method used in this research is a quantitative approach based on secondary data. The data used in this research is a time series which includes data from November 2022 to September 2023, totaling 11 data. From the data that has been collected, calculations are carried out using the Capital Asset Pricing Model (CAPM). The results of this research show that PT Bank Syariah Indonesia Tbk (BRIS) shares are defensive stock. With this research, it is hoped that investors will be able to know the level of risk in a stock before starting to invest. It is hoped that this research can be used as a source of thought when investors want to invest in PT Bank Syariah Indonesia Tbk (BRIS) shares.